Lyric Voice and Its Haunting Others - Milanko, Andrea (2010)
Although stability and coherence of lyric voice/speaker/subject were questioned as early as in modernist poetry postmodern poetry brings back into analytical consideration various discursive practices that undermine the final authority of the lyric subject. Lyric subject and its spectres of meaning that haunt it could possibly be more appropriately articulated and analysed in terms of Lacanian psychoanalysis. Namely literary critics of Russian formalism and New Criticism tried to emancipate the lyric speaker from any contextual influence arguing that its limits correspond to text production only. It was the lyric speaker who represented the final authority of meaning, while literary critics were conveniently focused more on the form of poems, allegedly for its ability to sustain the unity of meaning. However, postmodern poetry has again raised the question of meaning in poetry by activating other strata of signification (titles, parody, irony, visual media insertion, introduction of other voices in a poem, etc.), which cannot be attributed to the lyric subject, especially if they are turned against it. Having undertaken this particular kind of code manipulation, postmodern authors have explicitly involved context in the production of meaning. Text analysis cannot neglect these interventions, which additionally frame the lyric subject. The question is then whom we are to attribute responsibility for subversion of meaning, especially when it is done by means of parody or irony? Is it a new textual category superimposed on to the lyric subject, its denied “Other“, or are we to ascribe it to the author? Since consciousness and intention, be it author's or reader's, have not been favored among critics in terms of methodology, what is left to consider is text consciousness and its denied Others.
Projekt MZOS
ENG